Clinical Practice Guidelines as Evidence In Proving Medical Negligence - Fransisren Fransisren; Waty Suwarty Haryono; Herkutanto Herkutanto; Retno Kus Setyowati (Asian Journal of Social and Humanities, 2024)
Medical negligence is a doctor's failure to provide a standard of care that results in harm to the patient. The difference in the concept of negligence in the Criminal Code and the lex specialist Law No.17 of 2023 is in the legal standing of the basis for proving medical negligence. Articles 359 and 360 of the Criminal Code do not involve PPK. In Article 280 paragraph (2) jo Article 291 paragraph (1) of Law No.17 of 2023, it is explained that to avoid impacts that can harm medical personnel and hospitals, services must be carried out as a form of best effort, which is by norms, service standards, professional standards, and patient needs. Proof of whether or not the doctor commits negligence must be present in the PPK and medical records. In many criminal and civil cases in court in terms of evidence, the judge has ruled out PPK as evidence of letters. The research method in this research uses juridical-normative research. The results of the research are the requirements for proving medical negligence according to Law No.17 of 2023, which must fulfill legal obligations, violations of obligations, injuries, and causality. Proof of medical negligence in hospitals can use PPK as evidence if it fulfills the formal and material legal requirements. The formal requirement is if the PPK is by the legislation. The material requirement is if the PPK is prepared according to science, namely the National Guidelines for Medical Services (PNPK).